Design and Simulation of Lead-Acid Battery - Raji, Shahad; M. Kubba, Zainab (Al-Nahrain Journal of Science, 2020)
This research intends to design and simulation a model of "Lead-acid battery" using OrCAD PSPICE. It can be used for most renewable energy systems applications. The circuit simulator PSPICE is used to compose battery model at Voc 12V, Isc 4.8A, and six cells at 25 °C. This model has treated the battery parameters as the SOC, battery voltage and temperature of the battery at a charge and discharge state. The simulation results were compared with the battery datasheet, and it showed good agreement. The battery model of lead-acid is defined in the PSPICE library, so it could be used for most renewable energy systems applications.